Mind the gap, please! The effect of temporary help agencies on the consequences of work accidents - Carlos Garcia-Serrano; Virginia Hernanz; Luis Toharia (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Using data from a Spanish register on work-related accidents, this paper analyses the effect of contract types on two consequences of accidents: the probability of suffering a serious/fatal accident and the number of working days lost after an accident has happened. The focus is on the difference among temporary workers hired through temporary help agencies, direct temporary workers and open-ended workers. We find that workers hired through temporary help agencies are less likely to suffer serious/fatal accidents and the durations of their absences are shorter when they are, compared with workers holding either open-ended contracts or direct temporary contracts once personal, job and accident characteristics are controlled for.
Keywords: 330